NutriPlay: Bilingual Mobile App for Nutrition and Cultural Food Education - Falinda Oktariani; Yessi Marlina; Nufus Rahmatullah; Nur Kholis (JURNAL PROTEKSI KESEHATAN, 2026)
Digital nutrition education interventions have shown promise, yet most remain monolingual and rarely integrate local cultural food content, limiting their relevance in multilingual, culturally diverse settings such as Indonesia. This study addresses this gap by evaluating NutriPlay, a bilingual (Indonesian-English) mobile application that uniquely integrates nutrition education, English vocabulary acquisition, and Indonesian cultural food awareness—a combination not previously examined among elementary school students. A quasi-experimental one-group pre-post intervention study involved 30 fifth-grade students in Pekanbaru, Riau. Overall nutrition knowledge improved significantly from 37.2% to 83.1% (mean gain +45.9%, t(29)=18.47, p<0.001, Cohen's d=3.37, η²=0.92). Bilingual vocabulary mastery increased from 15.3% to 73.2% (+57.9%), and cultural awareness of Indonesian traditional foods reached 84%. Application engagement exceeded benchmarks with 95% repeat-use and mean session duration of 17.2 minutes. These findings demonstrate that a single mobile application can simultaneously advance nutrition literacy, second-language acquisition, and cultural identity in resource-limited school settings, offering a novel, scalable model for integrated health-language education in similar contexts